Impact of electrification on children's nutritional status in rural Bangladesh - Tomoki FUJII (Institutional Knowledge at Singapore Management University, 2018)
Access to electricity has the potential to improve the nutritional status of children by a variety of pathways such as increased wealth, reduced fertility through the change in time use, spread of information through technology such as TV, and improved health care services. Yet, the relationship between electrification and children’s nutritional status is rarely explored in the literature. We attempt to fill this lacuna by offering microeconometric evidence from rural Bangladesh, where a rapid expansion of electrification and significant improvement in children’s nutritional status were observed in the past two decades. We find that access to electricity has a positive impact on the nutritional status of children under five as measured by height-for-age Z-score (HAZ) by around 0.1–0.2 points using five rounds of Bangladesh Demographic and Health Survey from 2000 to 2014. Our results also appear to indicate that the quality of electricity may influence the size of this positive impact. While our analysis of causal pathways is limited by the data availability, it suggests that the positive impact of electrification partially comes from increased wealth. For some years, the positive impact can also be attributed to reduced fertility and information exposure through TV viewing. On the contrary, we find little evidence that the impact is attributable to the improvement of local health facilities. Our findings underscore the importance of evaluating infrastructure programs such as rural electrification from a broad perspective as their impacts may go well beyond the economic benefits considered in a typical cost–benefit analysis. This in turn may encourage governments to invest more in basic infrastructure, which is still severely lacking in Bangladesh and many other countries in the rest of South Asia and sub-Saharan Africa.